Analisis Nilai Perusahaan Ditinjau dari Harga Jual dan Return On Asset (ROA) Melalui Nilai Ekuitas Pada PT. Ace Hardware Tbk. - Kiki Kiki; Abdullah Abdullah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
this study, confirmation of the company's value theory is a reflection of the company's selling price in the company from the perspective of the market or society and the company's value is the selling price of goods when the goods will be sold. Thus this study uses the ratio analysis method and statistical analysis using the Smart PLS benchmark.The results of the study found that the company's value is not only seen from the selling price but how the company returns assets that provide value to equity, the company's value will always be high.